TINJAUAN KETERSEDIAAN INFRASTRUKTUR TERKAIT IMPLEMENTASI KEBIJAKAN PENYERAHAN PEMBERITAHUAN PABEAN MELALUI INTERNET - agung tri safari (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2019)
Submission of Customs Declaration including matters regulated in the Customs Law. Furthermore, this matter is further elaborated based on the Minister of Finance Regulation. Customs Declaration can be submitted in writing on the form or in the form of Electronic Data. For those in the form of Electronic Data, it is delivered by submitting Electronic Data storage media in the form of diskettes or etc to the Customs Office or through an Electronic Data exchange system. DJBC has issued a policy related to the full implementation (Mandatory) of the submission of customs declaration documents through the PDE system based on KEP-415 / BC / 2016 and began to be implemented effectively on January 1, 2019. The purpose of this study is to evaluate whether this policy can be applied in all regions of Indonesia This research is descriptive with a qualitative approach. Based on secondary data, not all regions of Indonesia are affordable to the internet network. The constraints on the availability of infrastructure are a necessity that must be anticipated. The results of this discussion can be input into the improvement of related policies.